The physical effects associated with Chelyabinsk meteorite's passage - Chernogor, L.F.; Rozumenko, V.T. (Вопросы атомной науки и техники, 2013)
The main effects associated with the February 15, 2013 Chelyabinsk bolide (Chebarkul meteorite) have been estimated. The major amount of energy release (approximately 0.2 Megaton) occurred near 25 km altitude where the rate of mass loss attained 20 kiloton s⁻¹, and the optical emission energy of 375 TJ. The pressure behind the shock near the bolide explosion epicenter attained a few kilopascals. The surface area of partial destructions was equal to approximately 6,000 km². The bolide explosion gave rise to appreciable disturbances not only in the lower atmosphere, but also in the upper atmosphere at a range of not less than 1,000…2,000 km. The effects in the geomagnetic field reached 0.5…1 nT. The earthquake caused by the bolide explosion had a Richter magnitude of 3-4. Оцінено основні ефекти, що супроводжували падіння Челябінського боліда (Чебаркульського метеорита) 15 лютого 2013 р. Показано, що основне енерговиділення (близько 0.2 Мт) мало місце близько висоти 25 км, де швидкість втрати маси досягала 20 кт/с, енергія оптичного свічення – 375 ТДж. Близько епіцентру вибуху боліда тиск у фронті ударної хвилі становив одиниці кілопаскалей. Площа зони часткових руйнувань будівель була близька до 6 тис. км². Вибух боліда призвів до помітного збурення не лише нижньої, а й верхньої атмосфери на віддаленнях не менше 1…2 тис. км. Розмір геомагнітного ефекту склав 0.5…1 нТл. Магнітуда землетрусу, викликаного вибухом боліда, не перевищувала 3-4. Оценены основные эффекты, сопровождавшие падение Челябинского болида (Чебаркульского метеорита) 15 февраля 2013 г. Показано, что основное энерговыделение (около 0.2 Мт) имело место вблизи высоты 25 км, где скорость потерь массы достигала 20 кт/с, энергия оптического свечения – 375 ТДж. Вблизи эпицентра взрыва болида давление во фронте ударной волны составляло единицы килопаскалей. Площадь зоны частичных разрушений построек была близка к 6 тыс. км². Взрыв болида привел к заметному возмущению не только нижней, но и верхней атмосферы на удалениях не менее 1…2 тыс. км. Величина геомагнитного эффекта составила 0.5…1 нТл. Магнитуда землетрясения, вызванного взрывом болида, не превышала 3-4.